2011
DOI: 10.1371/journal.pone.0023300
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of RSG-1.2 Peptide Binding to RRE-IIB RNA Element of HIV-1 over Rev Peptide Is Mainly Enthalpic in Origin

Abstract: Rev is an essential HIV-1 regulatory protein which binds to the Rev responsive element (RRE) present within the env gene of HIV-1 RNA genome. This binding facilitates the transport of the RNA to the cytoplasm, which in turn triggers the switch between viral latency and active viral replication. Essential components of this complex have been localized to a minimal arginine rich Rev peptide and stem IIB region of RRE. A synthetic peptide known as RSG-1.2 binds with high binding affinity and specificity to the RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
4
2
Order By: Relevance
“…These Δ H values are much higher than those reported for a Zn-finger-IIB interaction (−7.2 kcal/mol at 298 K) 37 and an in vitro selected peptide, RSG1.2-IIB interaction (−13.9 kcal/mol at 298 K) 38 under similar conditions (temperature, salt, pH). This is likely due to the coupled folding and RNA-binding of the unstructured free ARM, which can contribute significantly to the observed Δ H (and also to the unfavorable T Δ S ).…”
Section: Resultscontrasting
confidence: 59%
“…These Δ H values are much higher than those reported for a Zn-finger-IIB interaction (−7.2 kcal/mol at 298 K) 37 and an in vitro selected peptide, RSG1.2-IIB interaction (−13.9 kcal/mol at 298 K) 38 under similar conditions (temperature, salt, pH). This is likely due to the coupled folding and RNA-binding of the unstructured free ARM, which can contribute significantly to the observed Δ H (and also to the unfavorable T Δ S ).…”
Section: Resultscontrasting
confidence: 59%
“…Structural studies have shown an alpha helix at the major groove of RRE–RNA complex, and this interaction is sequence base‐specific with supplementary electrostatic contacts with phosphate backbone . The specificity of RSG‐1.2 peptide binding to RRE‐IIB RNA element of HIV‐1 surpassing REV peptide is enthalpic in origin as reported by previous studies …”
Section: Introductionsupporting
confidence: 67%
“…In another study, the binding of the Rev peptide to the HIV-1 RRE RNA is shown to be enthalpy driven as compared to the RSG-1.2 binding to the RRE RNA which is favored entropically. 18 The present study is the next step towards a better understanding of the energetic basis of molecular interactions between RNA and peptides. Here we explore the thermodynamic and solvent dynamic parameters of BIV TAR RNA and Tat interactions through various calorimetric and spectroscopic measurements.…”
Section: Introductionmentioning
confidence: 92%
“…There are many reports revealing the intricacies of the thermodynamic basis of complex formation of RNA and small molecules like aminoglycosides [14][15][16] and peptides. 17,18 The solution structure of BIV TAR RNA and the TAR-Tat complex is well characterized through NMR and molecular dynamics studies. 19,20 Tat binds with BIV TAR RNA in a b-hairpin loop structure in the major groove.…”
Section: Introductionmentioning
confidence: 99%